The difficult patient: An attachment perspective - A. Panzer; M. Viljoen; R.G. Maunder; J.J. Hunter (South African Family Practice)
Stressors such as illness, injury and hospitalisation are likely to accurate attachments behaviours. The way people react to these stressors (i.e their illness behaviour); varies widely; and is strongly correlated with their attachment style. In this paper we briefly review attachment theory, with reference to difficult patient behaviours, including compulsive self-reliance, compulsive care seeking and rejection of staff coupled with exaggerated help-seeking behaviour. We conclude by suggesting simple interventions that can easily be applied to enable staff to cope, and thus be more able to help patients with difficult illness behaviours.